Mapping the barrier of halal food industry performance and the policy insight: combination of ISM-DEMATEL approach - Susanty Aries; Puspitasari Nia Budi; Mariana Shinta Devi; Fekete-Farkas Mária; Gyenge Balázs; Nazaruddin La Ode (Engineering Management in Production and Services)
The study aims to understand interlinkages and the relative importance of barriers to maximising the performance of the halal industry in Indonesia using Integrated Interpretive Structural Modelling (ISM) and the Decision-Making Trial and Evaluation Laboratory (DEMATEL) methodology. This study uses the content validity method to find the relevant or valid barrier, the ISM methodology to examine the interrelationship between the valid barriers, and the DEMATEL methodology to find the cause–effect relationships and revise the ISM digraph. To the best of the authors’ knowledge, this study is the first to investigate the barriers to systematically maximising halal industry performance in Indonesia, elaborating on the relationship between relevant theories and practical issues to identify the barriers. The study’s integrated approach helps corporate and political decision-makers identify essential barriers to development and explore the interdependencies between barriers. This can help decision-makers overcome critical obstacles, use resources more efficiently, and find innovative solutions for the industry’s viability and dynamic development.